rug Prevention And Rehabilitation In The Context Of Local Law - Kamariah, A.M. Mimi (Journal of Malaysian and Comparative Law, 2019)
The drug problem in Malaysia is not a new one. What started in the early nineteenth century as a habit for the consumers with economic benefits for the British adminstrators, has grown to be the number one enemy of the country. In 1984, of the 11,915 cases reported, 63.2% were in the 20 to below 29 years age category while 10.4% were in the below 19 years age category. In 1985, up to May, 1,871 cases were reported out of which 62.5% were in the first age category and 9.2% in the second age category.